The Use of Indonesian Literature Learning as Character Building for Early Children - Laelina, Tri (International Proceedings of Nusantara Raya, 2023)
This study aims to introduce learning Indonesian literature from an early age. The research method used using the method of literature review (library research). This research based on various previous research result and collects several opinions from experts in the field of early childhood. With the study of Indonesia, literature it is hoped that early childhood will be able to grow and develop into children who have strong characters, are cultured, are independent, are able to express, themselves through their thoughs well, have broad insight, are critical, responsible, are refined with good manners, and have polite and well-mannared character. Learning Indonesian literature must be advanced through formal education and non-formal education. In learning Indonesia literature there is a connection, because both need and complement each other. It has the characteristics of language in Indonesian literature, namely the aesthetic aspect.